Pengaruh Ukuran Pemerintah, Opini Audit Dan Terpilihnya Kembali Kepala Daerah Sebelumnya (Petahana) Terhadap Audit Delay Pada Pemerintah Provinsi Di Indonesia - Abriany Vanesha; Efrizal Syofyan (Universitas Negeri Padang, 2020)
Financial statements that were not provided on time may cause those report loses their capacity to influence decisions. This study aims to examine the effects of goverments size, audit opinion, incumbent on audit delay in indonesia. This study used 165 financial reports from 33 provincial goverment in indonesia from 2014-2018. Researc data was obtained from the financial audit agency and directorate general of financial balance. The dependent variable of this researc is audit delay. While the independent variables include the size of goverment, audit opinion dan incumbent. Multiple regresion analysis was used to tes the hypothesis. The test results show that audit opinion has a significant effect on audit delay. But size of goverment and incumbent does not have a significant effect on audit delay.